2016
DOI: 10.1016/j.clinthera.2016.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Alarmins and Antitumor Immunity

Abstract: Accumulating data suggest that certain alarmins, High-mobility group nucleosome-binding protein 1 (HMGN1) in particular, contribute to the generation of antitumor immunity. Some alarmins can also be used as cancer biomarkers. Therefore, alarmins can potentially be applied for our fight against cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 151 publications
(198 reference statements)
0
30
0
1
Order By: Relevance
“…Elevated levels of alarmins can be seen in acute and chronic inflammatory conditions as well as certain types of cancer, especially that High Mobility Group Box 1 (HMGB1) and IL-33 are known to play roles in antitumor immune response [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of alarmins can be seen in acute and chronic inflammatory conditions as well as certain types of cancer, especially that High Mobility Group Box 1 (HMGB1) and IL-33 are known to play roles in antitumor immune response [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The function of these proteins in transcription, DNA repair and cancer progression have been partly established (3,4,17,18). The results of recent studies have demonstrated that HMGN1 may be a promising clinical biomarker for several types of cancer (19,20). Similarly, the expression of HMGN5 (previously known as NSBP1) is highly regulated in various types of human cancer, including prostate, bladder, breast, lung and clear-cell renal-cell carcinoma (21).…”
Section: Discussionmentioning
confidence: 99%
“…The alarmins are constitutively available endogenous molecules released from the granules, cytosol, or nucleus of cells by cell injury or other stimuli. In the extracellular milieu, they function as intercellular signals that mobilize cells by interacting with chemotactic receptors such as G-protein-coupled receptors (GiPCRs) and, in addition, activate cells by interacting with receptors such as Toll-like receptors (TLRs) (Nie et al 2016). It has been very surprising that chromatin-binding proteins such as HMGB1, HMGN1, IL-33, and IL-1α also have extracellular functions and are potent in inducing the production of proinflammatory cytokines.…”
Section: Novel Cytokinesmentioning
confidence: 99%